RANCANG BANGUN JARINGAN SITE TO SITE VPN (VIRTUAL PRIVATE NETWORK) DENGAN PROTOCOL OPENVPN - Usanto Usanto (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
The use of wireless media such as the internet in building computer networks is so widely used. However, performance and security must also be considered. VPN (Virtual Private Network) is one of the methods in network security that works by creating a tunnel so that a trusted network can connect to networks outside via the internet. PT. Laris Manis Utama is a private company engaged in the field of fresh fruits export-import and distributor. And already has several branch offices located outside the city. Designing a VPN (Virtual Private Network) with a Site to site (OpenVPN) system at PT. Laris Manis Utama functions as a communication liaison for media and data transfer between the head office server and branch servers so that they are connected in real-time and can develop application systems and updated databases